Engineered tungsten oxide-based photocatalysts for CO2 reduction: categories and roles. Issue 40 (8th October 2021) - Yang, Ge; Zhu, Xueteng; Cheng, Gang; Chen, Rong; Xiong, Jinyan; Li, Weijie; Wei, Yuechang
Abstract : This review focuses on the categories and roles of tungsten oxide-based photocatalysts in CO2 photoreduction. Abstract : Photocatalytic technology can convert CO2 molecules into clean fuels by solar energy, which can alleviate the energy and environmental crises caused by the consumption of fossil fuels and the greenhouse effect. It is extremely challenging to develop semiconductor photocatalytic materials to achieve high-efficiency catalysis of CO2 reduction with a suitable band gap, effective use of sunlight, and better oxidation–reduction capability for photogenerated holes and electrons. Tungsten oxides mainly exist in the form of WO3, W18 O49 (or WO2.72 ), WO3 ·0.33H2 O, etc., and their visible light response and suitable band structure have certain potential in the photocatalytic CO2 reduction process. At the same time, in view of the significance of the negative conduction band position, the strong CO2 adsorption capacity, and the rapid electron–hole separation, the crystal facet/crystal phase/structure/defect/composition of tungsten oxides can be engineered to treat their surfaces/interfaces to improve their catalytic activity. In this review, we first briefly introduce the different methods of controlling tungsten oxide. Then, the activities and mechanisms of different types of tungsten oxide-based photocatalyst in catalytic CO2 reduction are summarized. Finally, solutions to the problems for the material design and application of tungsten oxide-based photocatalysts in high-efficiency catalytic CO2 reduction are proposed, and future prospects are discussed.